1988
DOI: 10.1111/j.1445-5994.1988.tb02237.x
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone‐induced Hyperthyroidism: Assessment of the Predictive Value of Biochemical Testing and Response to Combined Therapy Using Propylthiouracil and Potassium Perchlorate*

Abstract: In order to assess the value of thyroid function testing during amiodarone therapy, we reviewed all available tests in 128 patients treated with this drug. Nine patients (7.0%) developed biochemical hyperthyroidism with elevation of both free thyroxine index (FT4I) and free triiodothyronine index (FT3I) and marked suppression of serum thyroid stimulating hormone (TSH) after 1-46 months of therapy; six of these nine patients had clear clinical evidence of thyroid overactivity. Where serial tests were available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
4

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
3
32
0
4
Order By: Relevance
“…czynność tarczycy indukowana AMIO zwykle wystę-puje po kilku miesiącach leczenia AMIO, ale może też wystąpić w ciągu kilku początkowych tygodni leczenia [32]. Początek AIT zależy od typu AIT, krótszy jest w przypadku typu 1 niż w typie 2 (patrz poniżej) [33].…”
Section: Szkolenie Podyplomoweunclassified
See 1 more Smart Citation
“…czynność tarczycy indukowana AMIO zwykle wystę-puje po kilku miesiącach leczenia AMIO, ale może też wystąpić w ciągu kilku początkowych tygodni leczenia [32]. Początek AIT zależy od typu AIT, krótszy jest w przypadku typu 1 niż w typie 2 (patrz poniżej) [33].…”
Section: Szkolenie Podyplomoweunclassified
“…AIT usually develops after months of AMIO treatment, but it can develop in the first few weeks of therapy [32]. The onset time of AIT depends on AIT type, being shorter in type 1 than in type 2 AIT (see below) [33].…”
Section: Amiodarone-induced Thyrotoxicosismentioning
confidence: 99%
“…Perclorato de potasio (KClO4) ha sido asociado con anemia aplásica, pero ningún caso ha sido informado cuando se ha usado para tratar TIA 1. En los pacientes que reciben grandes dosis de DAT más KClO4, parece razonable recomendar el monitoreo bisemanal del recuento leucocitario (27,28) .…”
Section: Perclorato De Potasiounclassified
“…Studies have shown that discontinuation of perchlorate from the combination therapy after about 6 weeks for patients on amiodarone therapy can achieve euthyroidism within 2 -5 weeks. 66,72 Perchlorate has serious adverse effects including agranulocytosis and aplastic anaemia as well as renal impairment at doses exceeding 1 g daily. 44 It is relatively safe at lower doses and that the dosage is tapered or stopped after about Lithium is concentrated by the thyroid and inhibits thyroidal iodine uptake.…”
Section: Amiodarone-induced Thyrotoxicosismentioning
confidence: 99%
“…65 SHBG levels may also be increased in AIT patients. 66 Subclinical hyperthyroidism may occur in those without symptoms whose serum TSH levels are suppressed with T 3 remaining within the reference range. Distinguishing the two AIT subtypes may be difficult on clinical grounds but clinical indicators may help differentiate.…”
mentioning
confidence: 99%